2013
DOI: 10.1093/ajh/hpt177
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol Downregulates Myocardial Renin-Angiotensin and Fibroblast Growth Factor Expression and Attenuates Cardiac Hypertrophy in Uremic Rats

Abstract: Uremic cardiac hypertrophy is associated with activation of the myocardial RAS and the FGFR-1. Downregulation of these genes induced by Pc and E results in similar amelioration of left ventricular hypertrophy despite the different antihypertensive effects of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 39 publications
6
33
0
Order By: Relevance
“…Furthermore, in a Zebrafish model of cardiac regeneration following myocardial ablation, expression levels of FGFR2 and FGFR4 are increased (57). Finally, in cardiac hypertrophy associated with kidney injury (also called uremic cardiomyopathy and discussed in more detail below), cardiac FGFR4 and FGFR1 levels are significantly elevated in patients (42) and rat models (58), respectively. In this scenario, FGFR4 activation and subsequent PLCγ/calcineurin/NFAT signaling seems to promote cardiac hypertrophy (41, 59).…”
Section: The Role Of Fibroblast Growth Factor Receptors In the Heartmentioning
confidence: 99%
“…Furthermore, in a Zebrafish model of cardiac regeneration following myocardial ablation, expression levels of FGFR2 and FGFR4 are increased (57). Finally, in cardiac hypertrophy associated with kidney injury (also called uremic cardiomyopathy and discussed in more detail below), cardiac FGFR4 and FGFR1 levels are significantly elevated in patients (42) and rat models (58), respectively. In this scenario, FGFR4 activation and subsequent PLCγ/calcineurin/NFAT signaling seems to promote cardiac hypertrophy (41, 59).…”
Section: The Role Of Fibroblast Growth Factor Receptors In the Heartmentioning
confidence: 99%
“…In addition, 1,25(OH) 2 D 3 downregulates AT 1 R expression in both cultured adipocytes (294) and renal arteries from hypertensive patients (114). Very recently, paricalcitol (a vitamin D analog) downregulated the myocardial renin, angiotensinogen, and fibroblast growth factor receptor-1 expressions in rats that were made uremic by 5/6 nephrectomy (143).…”
Section: The Klotho-vitamin D-ras Connectionmentioning
confidence: 99%
“…Animal studies (mice) have shown that the 1,25(OH) 2 D-VDR complex negatively regulates renin expression, and that this vitamin D-induced reduction in RAAS activity can prevent adverse vascular outcomes to a similar extent induced by pharmacologic angiotensin-receptor antagonism(15, 87-93). Human studies have supported this theory, demonstrating that low circulating vitamin D concentrations are associated with higher plasma renin activity and angiotensin II concentrations(86, 94, 95), and that vitamin D deficiency is associated with higher RAAS activity that can be lowered following intervention with vitamin D 3 therapy(72, 94, 96).…”
Section: Introductionmentioning
confidence: 99%